TERAPI TAWA DALAM MENURUNKAN KELUHAN EMESIS GRAVIDARUM - Neny Dwi Pebriasanty; Mira Triharini; Ni Ketut Alit (Universitas Airlangga, 2014)
Emesis Gravidarum or nausea and vomiting during pregnancy is a common complaint submitted by pregnant women inearly pregnancy. Laughter therapy is a therapy that can cause effects happy, excited, comfortable, and can solve avariety of problems as well as psychological health. This therapy led to increased serotonin hormone that can suppressnausea and vomiting in pregnant women. The aim of this study was to analyze the effect of laughter therapy to decreaseEmesis Gravidarum complaints in pregnant women. The study used Pre-Experimental as a design. Population ispregnant women having experience of emesis gravidarum in Rumah Sakit Marinir Gunung Sari Surabaya. 18respondents are choosen by purposive sampling technique. The independent variable is laughter therapy and thedependent variable are reduction of nausea and vomiting. Data collected by questionnaires with level of significant alpha≤ 0.05. The result shows p=0.002 (α <0.05). It indicates that there were a significant decrease in nausea andvomiting in pregnant women experiencing emesis gravidarum after getting laughter therapy. It can be concluded thatthere were significant level of decreasing nausea and vomiting by laughter therapy in pregnant women with emesisgravidarum. This therapy can be used continuously. Further studies are expected to be expanded sample and thepresence of the control group.